Surgical Closure of Sacral Pressure Sores by Gluteal Skin Flap. (Bangladesh Journal of Plastic Surgery, 2014)
Pressure sores are an ancient medical problem; even found during autopsies of Egyptian mummies. This prospective study was carried out in the Department of Plastic Surgery, Dhaka Medical College & Hospital (DMCH), Dhaka between January 2012 to December 2012 to evaluate the outcome of surgical closure of sacral pressure sores by Gluteal skin flaps. Twenty two patients admitted into DMCH with stage III & IV sacral pressure sores were included. Over two-thirds (68.2%) of the ulcers were in Stage-III and over three-quarters (77.3%) had signs of local infection. The average horizontal and vertical lengths of the defects before excision were 10.4 and 8.8 cm respectively which increased to 12.6 and 10.6 cm respectively after excision of dead and devitalized tissues. The average medial advancement of the flap was 6.3 cm. Postoperative flap-monitoring did not reveal infection, seroma or hematoma in any of the patients. Only 2(9.1%) patients had marginal flap loss. Marginal flap losses developed in two cases were excised and direct-suturing (secondary closure) were done. More than 90% of the patients exhibited good outcome. The study concluded that Gluteal skin flap produces good result in majority of the patients with large sacral sores with almost no complications or recurrences. The Gluteal skin flap has the advantages of muscle sparing, less donor site morbidity, versatility in design and less effort to harvest DOI: http://dx.doi.org/10.3329/bdjps.v4i1.18684 Bangladesh Journal of Plastic Surgery January 2013, 4(1): 05-09